Rancangan Sistem Penilaian Kinerja Perpustakaan Berbasis Indikator Kinerja Iso 11620:2008 Pada Layanan Terbuka Perpustakaan Nasional RI - Wakhid, Abdul; Sitanggang, Imas Sukaesih; Saleh, Abdul Rahman (Perpustakaan IPB, 2015)
Library performance measurement is one of a strategy to evaluate utilization of library resources. The objective of this study was to identify indicators needed to measure the performance and to design an counting system measurement at Open Service at National Library of Indonesia. The measurement indicators were based on ISO 11620:2008 consisting of 45 indicators. It was selected 10 indicators: 1) percentage of required titles in the collection (RTC); 2) shelving accuracy (SA); 3) staff per capita (LS); 4) collection turnover (CT); 5) loans per capita (LPC); 6) in-library use per capita (IUC); 7) library visits per capita (LVC); 8) percentage of target population reached (PTPR); 9) user satisfaction (AUS); 10) user services staff as a percentage of total staff (USSPTS). The indicators were selected through four stages: 1) selecting indicators related to activities in the Indonesia National Library and removing indicators related to activities that are not conducted in the institution; 2) removing indicators related to cost; 3) identifying and selecting indicators related to vision and mission by the questionnaire; 4) analizing the results of the questionnaire and setting the indicators that have an average value of the results greater than 0 as an selected indicator. The results of managements attitude that required the a performance counting system. System design was developed based on the system requirements and management’s needs. The system that was able to process data into information of performance. The system was integrated with the integrated national library system (INLIS) and the data that were not available in INLIS were manually input. Steps of system developing were defining use case, description use case, activity diagram, class diagram, sequence diagram, object role/relational mapping and entity relationship diagram. Keywords: Information System, ISO 11620, Library, Performance Indicators